SUPEROITISMO NO MARANHÃO: os modos de fazer, temas e formas de falar e a invenção do cinema local como prática de micro resistências (1970/80). - CALDAS, Leide Ana Oliveira (2016)
The present work is inserted in the context of Social History and, more precisely, in the interface of this with other languages in the way of looking, treating and talking about daily life. Among languages we opted for Cinema. In this way, we will examine the discourse produced by cinema in Brazil, but specifically in São Luís , M aranh ão capital in the period between the 1970s and 1980s. The problem theme of the research is the discourses produced about the socio - historical dynamics of the city through ways of making and saying (Certeau), in this temporal cut, by local filmmakers and expressed in films m ade with the Super 8mm super - rated action. To do so, we will present the course of cinema in Brazil and Maranhão, with emphasis on film superoitist as micro resistances explaining the milestones of filmic practices exercised as micro liberties of its direc tors, occupying the space of filmmakers of the citizen; their clashes and the scenario in which they produced their films to then configure the discourse logic of this production from the local experience.